2019
DOI: 10.1080/09687599.2018.1547186
|View full text |Cite
|
Sign up to set email alerts
|

Overprotection in the lives of people with intellectual disability in Malta: knowing what is control and what is enabling support

Abstract: A study of overprotection in the lives of persons with intellectual disability in Malta was carried out on the principles of inclusive research. Focus groups were held with people with intellectual disability, parents of people with intellectual disability, and those working with persons with intellectual disability. Overprotection is a disabling barrier. Its effects were identified in employment, leisure time, intimate relationships, and the use of public transport, money, and mobile phones. People with intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 21 publications
4
54
1
1
Order By: Relevance
“…These opinions were expressed by Mark and Ninu and are consistent with similar findings from research carried out within a Maltese context by Azzopardi Lane and Callus (), Debattista () and Azzopardi Lane (). As also claimed by Callus and Bonello (), the absence of opportunities for supported community living and personal assistant services is one of the major deterrents to the autonomy of persons with learning disability in Malta. The latter typically spend most of their life living with their families, who support them till they are unable to care for them any longer.…”
Section: Resultscontrasting
confidence: 71%
See 4 more Smart Citations
“…These opinions were expressed by Mark and Ninu and are consistent with similar findings from research carried out within a Maltese context by Azzopardi Lane and Callus (), Debattista () and Azzopardi Lane (). As also claimed by Callus and Bonello (), the absence of opportunities for supported community living and personal assistant services is one of the major deterrents to the autonomy of persons with learning disability in Malta. The latter typically spend most of their life living with their families, who support them till they are unable to care for them any longer.…”
Section: Resultscontrasting
confidence: 71%
“…However, it is not a finding which is exclusive to this research. Several studies carried out in this context and others have reported an excessive amount of sheltering of persons with learning disability, often by parents, guardians and service providers (Azzopardi Lane & Callus, ; Callus & Bonello, ; Clark & O’toole, ; Debattista, ; Isler, Tas, Beytut, & Conk, ). In many instances, the overprotection described took the form of infantalisation, where participants reported that they were treated not as young adults but as children.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations